Indonesia Atmosphere And Image: Key Drivers Of Sales At MDC Mart - Shofuroh, Dewi Asiyatus; Ardana, Yudhistira; Yunarti, Yuyun (Oikonomia: Jurnal Manajemen, 2025)
Purpose This study aims to analyze the influence of store atmosphere and brand image on consumer purchasing decisions at one of the grocery stores in Lampung. Methodology This study uses quantitative methods and primary data obtained through an online survey using Google Forms from store consumers. The sample size obtained was 66 consumers and customers of the MDC grocery store selected by convenience sampling as respondents. Structural Equation Model (SEM) facilitated by SmartPLS software version 3.0 was used to analyze the data in this study. Findings The study's results indicate that store atmosphere does not significantly affect purchasing decisions. At the same time, brand image has a positive and significant effect on purchasing decisions. Suggestion Stores should focus more resources on strengthening brand image through effective communication and positive brand experiences, as they have been shown to significantly affect purchasing decisions. Meanwhile, the store atmosphere strategy should be re-evaluated, and other factors that may be more relevant to consumers should be examined. more representative results and maintain quality to reinforce the brand image.